A ‘disjunct’ in the linguistic landscape: Messages about food and nutrition in Indonesian school environments - Harbon, Lesley; Halimi, Sisilia Setiawati (Universitas Pendidikan Indonesia, 2019)
In Indonesia’s schoolscapes, messages regarding food and nutrition abound. The researchers conducted descriptive, evaluative research on the nature and scope of the linguistic landscape around 20 primary school grounds in Jakarta and Depok education districts. The purpose of this study was to gather (digitally) and analyze food/nutrition signs/texts in order to determine which languages are represented in which places, and the kinds of messages for each language. As well, the study explored other non-food images relating to health found in these schoolscapes. Data were analysed using open and axial coding. The study found that the majority of the texts and images are found to be in Indonesian and only a small percentage are in Sundanese, Arabic, Japanese and English. Texts relating to food and nutrition were found inside and outside the school environments. Each language was responsible for a particular type of message. Official (top-down) messages inside the schoolscapes advocate for healthy food and nutrition. Texts found outside the schoolscapes convey a variety of messages, healthy and otherwise: from food labels, and flavor, to cigarette advertising. There is a ‘disjunct’ between the overtly health-oriented linguistic landscape inside the school perimeter and the less healthy linguistic landscape outside the schoolscapes, an issue which may be of concern to schools and their communities.